Review of Staphylococcus aureus infections requiring admission to a paediatric intensive care unit. Issue 12 (21st November 2005) - Miles, F; Voss, L; Segedin, E; Anderson, B J
Abstract : Aims: To review clinical features and outcome of children with severe Staphylococcus aureus sepsis (SAS) presenting to a paediatric intensive care unit (PICU) with particular focus on ethnicity, clinical presentation, cardiac involvement, and outcome. Methods: Retrospective chart review of patients coded for SAS over 10 years (October 1993 to April 2004). Results: There were 58 patients identified with SAS over the 10 year study period; 55 were community acquired. This accounted for 4% of hospital admissions for SAS over this time; children with staphylococcal illness comprised 1% of all admissions to the PICU. Maori and Pacific children with SAS were overly represented in the PICU (81%) from a paediatric population where they contribute 21.6%. Musculoskeletal symptoms (79%) dominated presentation rather than isolated pneumonia (10%). An aggressive search for foci and surgical drainage of infective foci was required in 50% of children. Most children had multifocal disease (67%) and normal cardiac valves (95%); the few children (12%) presenting with methicillin resistant S aureus (MRSA) had community acquired infection. The median length of stay in the PICU was 3 (mean 5.8, SD 7.6, range 1–44) days. The median length of stay in hospital was 15 (mean 21, SD 22.7, range 2–149) days. Mortality due to SAS was 8.6% (95% CI 1.4–15.8%) compared with the overall mortality for the PICU of 6% (95% CI 5.3–6.7%). Ten children had significant morbidity after discharge. Conclusions: Community acquired SAS affects healthy children, is multifocal, and has high morbidity and mortality, in keeping with the high severity of illness scores on admission. It is imperative to look for sites of dissemination and to drain and debride foci. Routine echocardiography had low yield in the absence of pre-existing cardiac lesions, persisting fever, or persisting bacteraemia.